Physical-recreational activities and self-esteem in the elderly: Systematic Review - Alquinga Cuasquer, Marina Salome (MENTOR revista de investigación educativa y deportiva, 2025)
Ageing is a natural and biological process that involves a series of physical, psychological and social changes over time. During this stage, older adults face emotional changes that affect their self-esteem, manifesting certain feelings of loneliness, abandonment, insecurity, among others. In this situation, physical-recreational activities become important since several studies have shown that they contribute to eliminate tensions, fears and stress, favor sleep and mood, positively influencing their self-esteem and self-confidence. Therefore, the objective of this article was to systematize the theoretical and methodological foundations that support the benefits of physical-recreational activities on the self-esteem of older adults. The methodology used was a systematic review with the use of the PRISMA protocol. From the analysis of bibliographic sources published during the years 2019-2024, articles were selected in Spanish from databases such as: Dialnet, Redalyc, Scielo, Latindex. In summary, this article provides a theoretical framework that highlights the importance of physical-recreational activities in the self-esteem of the elderly. It also offers significant contributions to guide the familys, communitys, teachers and future professionals in the field of health.